2018
DOI: 10.3847/1538-4357/aaf164
|View full text |Cite
|
Sign up to set email alerts
|

The Advanced Spectral Library (ASTRAL): Reference Spectra for Evolved M Stars

Abstract: The HST Treasury Program "Advanced Spectral Library Project: Cool Stars" was designed to collect representative, high quality ultraviolet spectra of eight evolved F−M type cool stars. The Space Telescope Imaging Spectrograph (STIS) echelle spectra of these objects enable investigations of a broad range of topics including stellar and interstellar astrophysics. This paper provides a guide to the spectra of the two evolved M-stars, the M2Iab supergiant α Ori and the M3.4 giant γ Cru, with comparisons to the prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…circumstellar CO fourth-positive absorption bands and chromospheric emission lines. Figure 5 shows that starting from 1700 Å, the observed T Rad slowly increases toward shorter wavelengths (Carpenter et al 2018), as is observed for the Sun (Avrett & Loeser 2008, Fig . 1), albeit at lower values.…”
Section: Nlte Modeling Of the Fuv Radiation Fieldsupporting
confidence: 71%
See 1 more Smart Citation
“…circumstellar CO fourth-positive absorption bands and chromospheric emission lines. Figure 5 shows that starting from 1700 Å, the observed T Rad slowly increases toward shorter wavelengths (Carpenter et al 2018), as is observed for the Sun (Avrett & Loeser 2008, Fig . 1), albeit at lower values.…”
Section: Nlte Modeling Of the Fuv Radiation Fieldsupporting
confidence: 71%
“…olution Spectrograph (GHRS;Carpenter et al 1994 and the Space Telescope Imaging Spectrograph (STIS) of the HST (Carpenter et al 2018), and it is interesting to compare these observations with the FUV continuum generated by empirically derived VLA and ALMA radio temperature profiles. To do so, we performed time-independent nonlocal thermal equilibrium (NLTE) spherical radiative transfer computations for the formation of the Si I continua to the ground and first excited terms, which are expected to dominate the bound-free opacity between 1350 < λ(Å) < 1680.…”
Section: Nlte Modeling Of the Fuv Radiation Fieldmentioning
confidence: 99%
“…The FUV radiation field of Betelgeuse has been observed at high signal-to-noise ratio (S/N) with the Goddard High Resolution Spectrograph (GHRS) (Carpenter et al 1994) and the Space Telescope Imaging Spectrograph (STIS) of the HST (Carpenter et al 2018), and it is interesting to compare these observations with the FUV continuum generated by empirically derived VLA and ALMA radio temperature profiles. To do so, we performed time-independent nonlocal thermal equilibrium (NLTE) spherical radiative transfer computations for the formation of the Si I continua to the ground and first excited terms, which are expected to dominate the bound-free opacity between 1350 < λ(Å) < 1680.…”
Section: Nlte Modeling Of the Fuv Radiation Fieldmentioning
confidence: 99%
“…Alfvén waves have been found to be efficient in driving winds and produce clumpy mass loss from giant and supergiant stars (e.g. Vlemmings 2014; see also Hartmann & MacGregor 1982;Airapetian et al 2000;Suzuki 2007;Airapetian et al 2010Airapetian et al , 2015Yasuda et al 2019;Carpenter et al 2018, andFigure 7 in Rau et al 2018). In a weakly ionized but collisional shell, a propagating Alfvén wave would also involve the motion of the neutral species that are present in the shell.…”
Section: Alfvén Wavesmentioning
confidence: 99%